DEFINING BRAND IDENTITY OF NOESA WOVEN FABRIC THROUGH TOTAL BRANDING IN ONLINE MEDIA - Agus Daniar; Rustono Farady Marta; Angelia Sampurna (Pusat Penelitian dan Pengembangan Aplikasi Informatika, Informasi dan Komunikasi Publik (APTIKA dan IKP) Badan Penelitian dan Pengembangan SDM Kementerian Komunikasi dan Informatika, 2020)
Woven fabric is a handicraft product that has been passed down through generation. This fabric commonly used as traditional dance costumes at parties or traditional events. Along with the times, the variety of products produced from woven fabrics are keep growing. The interest and awareness of woven fabrics is gradually increasing, which can serve as an opportunity for industry players to highlight their products. This study aims to explore the brand identity of a local product that uses woven cloth as its basic material, namely Noesa. The method used in this research is a case study in qualitative approach with data collection techniques using observation methods, as well as documentation to obtain primary and secondary data. Data analysis techniques were carried out by reduction, presentation and drawing conclusion. The result shows that the strategy implementation through brand identity applied by Noesa is in line with total branding of marketing communication, which include aspects of Noesa's brand, Watobi craftsmen (suppliers), a variety of products in fulfilling the needs of the consuments (competitors) and various network through social media (distribution) in its marketing